Polysialic acid/neural cell adhesion molecule modulates the formation of ductular reactions in liver injury. Issue 5 (29th September 2014) - Tsuchiya, Atsunori; Lu, Wei‐Yu; Weinhold, Birgit; Boulter, Luke; Stutchfield, Benjamin M.; Williams, Michael J.; Guest, Rachel V.; Minnis‐Lyons, Sarah E.; MacKinnon, Alison C.; Schwarzer, David; Ichida, Takafumi; Nomoto, Minoru; et al.
<x xml:space="preserve">Abstract</x> In severe liver injury, ductular reactions (DRs) containing bipotential hepatic progenitor cells (HPCs) branch from the portal tract. Neural cell adhesion molecule (NCAM) marks bile ducts and DRs, but not mature hepatocytes. NCAM mediates interactions between cells and surrounding matrix; however, its role in liver development and regeneration is undefined. Polysialic acid (polySia), a unique posttranslational modifier of NCAM, is produced by the enzymes, ST8SiaII and ST8SiaIV, and weakens NCAM interactions. The role of polySia with NCAM synthesizing enzymes ST8SiaII and ST8SiaIV were examined in HPCs in vivo using the choline‐deficient ethionine‐supplemented and 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine diet models of liver injury and regeneration, in vitro using models of proliferation, differentiation, and migration, and by use of mouse models with gene defects in the polysialyltransferases (St8sia 2+/−4+/−, and St8sia2−/−4−/−). We show that, during liver development, polySia is required for the correct formation of bile ducts because gene defects in both the polysialyltransferases (St8sia2+/−4+/− and St8sia2−/−4−/− mice) caused abnormal bile duct development. In normal liver, there is minimal polySia production and few ductular NCAM+ cells. Subsequent to injury, NCAM+ cells expand and polySia is produced by DRs/HPCs through ST8SiaIV. PolySia weakens cell‐cell and cell‐matrix interactions, facilitating HGF‐induced migration. Differentiation of HPCs to hepatocytes in vitro results in both transcriptional down‐regulation of polySia and cleavage of polySia‐NCAM. Cleavage of polySia by endosialidase (endoN) during liver regeneration reduces migration of DRs into parenchyma. Conclusion: PolySia modification of NCAM+ ductules weakens cell‐cell and cell‐matrix interactions, allowing DRs/HPCs to migrate for normal development and regeneration. Modulation of polySia levels may provide a therapeutic option in liver regeneration. (Hepatology 2014;60:1727–1740)